Efficacy of Heptral® in the treatment of hepatic toxicity induced by cytostatic chemotherapy - A. V. Snegovoy; L. V. Manzyuk (Опухоли женской репродуктивной системы)
The efficacy of Heptral® (ademethionine) was evaluated in the treatment of chemotherapy-induced hepatotoxicity in 19 patients with various malignancies. Four-week administration of oral Heptral® 400 mg twice daily was shown to reduce the level of transaminases to normal values in 10 of 12 patients with grade 1 toxicity. Longer (2-to-4 month) use of Heptral® was required to normalize the level of transminases in grade 2 hepatotoxicity. The chemotherapy regimen was not changed during the use of this drug.